2012
DOI: 10.1039/c2sm07374a
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of lamellar liquid crystals in two and three dimensions: a simulation study

Abstract: We present large scale computer simulations of the nonlinear bulk rheology of lamellar phases (smectic liquid crystals) at moderate to large values of the shear rate (Peclet numbers 10 − 100), in both two and three dimensions. In two dimensions we find that modest shear rates align the system and stabilise an almost regular lamellar phase, but high shear rates induce the nucleation and proliferation of defects, which in steady state is balanced by the annihilation of defects of opposite sign. The shear rateγ c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 54 publications
3
21
1
Order By: Relevance
“…Oriented lamellae have been obtained in simulations of a coarsegrained molecular model for lipids, [25][26][27] while defect dynamics has been investigated in simulations of a phasefield model of a smectic-A system. 28 Onion and intermediate states have large-scale structures of the order of micrometers, which are beyond typical length scales accessible to molecular dynamics (MD) simulations of coarse-grained surfactant molecules. In our study, we employ a meshless-membrane model, [29][30][31][32] where a membrane particle represents not a surfactant molecule but rather a patch of bilayer membranein order to capture the membrane dynamics on a mi-crometer length scale.…”
Section: Introductionmentioning
confidence: 99%
“…Oriented lamellae have been obtained in simulations of a coarsegrained molecular model for lipids, [25][26][27] while defect dynamics has been investigated in simulations of a phasefield model of a smectic-A system. 28 Onion and intermediate states have large-scale structures of the order of micrometers, which are beyond typical length scales accessible to molecular dynamics (MD) simulations of coarse-grained surfactant molecules. In our study, we employ a meshless-membrane model, [29][30][31][32] where a membrane particle represents not a surfactant molecule but rather a patch of bilayer membranein order to capture the membrane dynamics on a mi-crometer length scale.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent viscosity is found to be a linear function of the number of defects in the system in the late stages of coarsening. 16 In large systems, it is observed that in addition to ordering, there is also the creation of defects due to shear, suggesting that a minimum size is required for the creation of defects. Moreover, for a given system size, there is a minimum strain rate 16 which is required for the formation of defects.…”
Section: Introductionmentioning
confidence: 98%
“…16 In large systems, it is observed that in addition to ordering, there is also the creation of defects due to shear, suggesting that a minimum size is required for the creation of defects. Moreover, for a given system size, there is a minimum strain rate 16 which is required for the formation of defects. Two different defect creation mechanisms, the extensional and the compressional mechanism, have been identified 15,16 in simulations.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations